NAKHAYCHUK OLEG, ZAKHAROVA ELINA, HOROBCHISHYNA VALENTINE, TSYRULNYK OKSANA - NAKHAYCHUK, OLEG; ZAKHAROVA, ELINA; HOROBCHISHYNA, VALENTINE; TSYRULNYK, OKSANA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
This work is devoted to the study of mechanical characteristics of textile fabrics in the process of their manufacture and processing, which is characterized by a phenomenon of heterogeneity (heterogeneity of properties in longitudinal and transverse directions). This phenomenon is due to the heterogeneity of physical, temperature, concentration, hydrodynamic, rheological and other factors. This heterogeneity increases with increasing the number of threads. Modern methods of studies of the influence of transverse uneven properties on the processes of deformation and destruction of a bundle of textile threads are generally time consuming, and they do not give quantitative information the influence of its components on the mechanical characteristics of products. Therefore, the implementation of studies regarding the study of the degree of influence of the transverse heterogeneity of the mechanical properties of textile threads on the peculiarities of the mechanics of their deformation and destruction, while with the development of forecasting methods are relevant and useful for the production of products. The authors of the article have developed a method of studying the strength of textile threads, which is characterized by the transverse heterogeneity of indicators of mechanical properties using mathematical modeling, which allows, without conducting labor intensive experimental studies, to predict its loss. The classification of indicators of mechanical properties by the degree of influence of their cross variations on the value of a break loading of a bundle of textile threads with developed prediction models developed respectively. The method of statistical imitation of tensile test was used, methods of mathematical analysis were used for the case of tightening of a bundle of textile threads. The developed mathematical model allows you to describe the influence of different variations on the break load and to classify different transverse variations of properties by the degree of influence on the characteristics of the strength of the thread bundle. The relationship between the strength realization coefficient and different transverse variations of mechanical properties is established, which made it possible to quantify the effect of heterogeneity of mechanical properties on the strength of textile filaments.